Respostas
respondido por:
10
a) f (3)
2.3² - 6 . 3 - 4
2.9 - 18 - 4
18 - 18 - 4
0 - 4
= - 4
3.3² - 5 . 3 + 1
3.9 - 15 + 1
27 - 15 + 1
12 + 1
= 13
b) f (-2)
2.(-2)² - 6 . (-2) - 4
2.4 + 12 - 4
8 + 12 - 4
20 - 4
= 16
3.(-2)² - 5 . (-2) + 1
3.4 + 10 + 1
12 + 10 + 1
22 + 1
= 23
c) f(0)
2.0² - 6 . 0 - 4
2.0 - 6 . 0 - 4
0 - 0 - 4
= - 4
3.0² - 5 . 0 + 1
3.0 - 0 + 1
0 - 0 + 1
= 1
2.3² - 6 . 3 - 4
2.9 - 18 - 4
18 - 18 - 4
0 - 4
= - 4
3.3² - 5 . 3 + 1
3.9 - 15 + 1
27 - 15 + 1
12 + 1
= 13
b) f (-2)
2.(-2)² - 6 . (-2) - 4
2.4 + 12 - 4
8 + 12 - 4
20 - 4
= 16
3.(-2)² - 5 . (-2) + 1
3.4 + 10 + 1
12 + 10 + 1
22 + 1
= 23
c) f(0)
2.0² - 6 . 0 - 4
2.0 - 6 . 0 - 4
0 - 0 - 4
= - 4
3.0² - 5 . 0 + 1
3.0 - 0 + 1
0 - 0 + 1
= 1
HyasCosta:
obrigado <3
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás